Antropometria de escolares ao ingresso no ensino fundamental na cidade de Belém, Pará, 2001 - NEVES, Olga Maria Domingues das (Universidade Federal do Pará, 2018)
Objectives: to perform anthropometric measurements in elementary school students of the public school system of the State of Belém, Pará, as a tool for nutritional surveillance and to study associations between nutritional status and biological, social and economic characteristics. Methods: 793 students were assessed for their nutritional status, by z scores of height/age and weight /height according to the World Health Organization criteria. Biological, social and economic variables were: gender, age, place of birth, age of school enrolment and maternal education level. The chi square test was used to relate nutritional status to variables. Results: of the 637 students assessed, 16.6% were of low stature or in risk of low stature, 4.5% malnourished or in risk of malnourishment, 7.4% were overweight or obese. There was no significant association between nutritional status and gender. The majority of the children was born in the capital, was enrolled late in school and had mothers with education level of >4 years. There was a significant correlation between obesity and low stature with low maternal education level; malnutrition risk and low stature with late school enrolment; and obesity and normal stature with regular enrollment. Conclusions: low maternal school level and late school enrollment are associated to nutritional problems. School nutritional surveillance is important to assess, treat and prevent children's health and nutrition risks.